Time and freedom in Education Some Latin American notes on the Manifesto for Education of Biesta y Säfström (Praxis Educativa, 2018)
This essay discusses Biesta and Säfström’s Manifesto for Education relation between time and freedom in education. I debate three theoretical nodes of this relation. First, I relate history of educational research in Latin America for demonstrate the strong theoretical and spatiallimitation of Biesta and Säsftröm concept and how temporal articulationsare similar in two antagonist perspectives: new educational theories and quality of education. Latter, is central in historical phenomena when educational research professionalization produce teachers deprofessionalization. Second, I argue how the temporal articulation based in the regime of historicity called presentism, reduce freedom possibilities in education, especially teacher’s freedom to be.  Finally, the political and theoretical principles of the proposal of Manifesto are shared, but it opposes universal temporary articulation that restricts divergent paths to diverse forms of freedom in the educational sphere.
Keywords: temporal articulations-educational freedom-Manifesto for Education. quality education-Latin America